(untitled) (Proceeding of SINERGY, 2026)
Local cultural products function simultaneously as market offerings and identity carriers, yet their tourism value is realised only when the destination system enables visitors to encounter, interpret, and consume them with minimal friction. This study develops and operationalises a parsimonious tourist-preference model for ulos-based cultural tourism products in Meat Tourism Village (Toba Regency, North Sumatra) by adopting a destination-product perspective that foregrounds two core levers: attractions (X1) and accessibility (X2). The structural model tests the direct effects of (i) attraction quality—expressed through interpretive clarity, participatory cultural experiences, and perceived authenticity—and (ii) accessibility—capturing travel effort, reliability, and within-site mobility—on tourist preference for ulos-based cultural tourism products (Y). The research is designed as an explanatory census survey of all tourists recorded by village management over one year (N = 300), and the model will be estimated using PLS-SEM (SmartPLS). The paper contributes an auditable construct specification and hypothesis set suitable for rural cultural-destination governance, while providing a practical diagnostic logic for destination managers by indicating whether experience enrichment (attractions) or friction reduction (accessibility) is the more decisive pathway for strengthening ulos-product preference.